Sustainable Menstrual Hygiene Practices and Their Environmental and Health Implications: A Systematic Review in the Indonesian Context - Azjuba, Aida Nurul; Alifa, Nadhira Silmi (International Journal of Social Service and Research, 2026)
Menstrual hygiene management (MHM) intersects with critical domains of public health, environmental sustainability, and gender equity, particularly in low- and middle-income countries (LMICs) such as Indonesia. Despite increasing global discourse, MHM and sustainable menstrual products remain underrepresented in national health and development agendas. Hence, their adoption and impact within the Indonesian context require further investigation. A systematic literature review was conducted following the PRISMA methodology to explore patterns, challenges, and public health implications associated with the use of sustainable menstrual products in LMICs. A total of seventeen studies were selected based on their methodological robustness, topical relevance, and specific focus on the use of reusable menstrual hygiene products. Multiple benefits were consistently reported, offering advantages such as improved user health outcomes, enhanced long-term cost efficiency, and reduced environmental hazards. However, utilization remained low across reviewed settings due to major barriers to implementation, including deficiencies in water, sanitation, and hygiene (WASH) infrastructure, persistent sociocultural taboos, limited market availability, and prevalent misconceptions regarding intravaginal product safety. An ongoing theme across studies was the observed disconnect between product awareness and actual use—a gap frequently attributed to fragmented health education initiatives. The findings underscore the potential of sustainable menstrual hygiene interventions to enhance both public health and ecological outcomes in Indonesia. Successful implementation is made possible through concurrent investments in foundational infrastructure, culturally responsive education, and multisectoral coordination, while systemic barriers must be addressed through integrated policy and community engagement strategies.